Modeling perceived quality of life for people living near a Nigerian dumpsite (2012)
In response to the rapid and unplanned growth that has led to the colocation of residential communities with refuse dumpsites in Lagos, Nigeria, we conducted a cross-sectional investigation of individuals living within the Olusosun community near a refuse dumpsite. Participants were 479 persons (>18 years of age, 52.6% male) who lived within 1 km of a refuse dumpsite. We examined the relationships between perceived quality of life and predictor variables, self-esteem, learned helplessness, and environmental expectations. Data analysis using structural equation modeling procedures partially supported our hypothesized explanatory model. Specifically, we found self-esteem had direct and indirect effects, through environmental expectations, on perceived quality of life. However, the indirect effect of learned helplessness on perceived quality of life was not supported. A limitation of our study, selective recruitment of participants who could read and write in English, emphasizes the need for future studies to recruit indigenous language speakers.